Psychological Safety, Wasathiyah, and the Intention of Violence: A Survey of UPI Students in the Context of Student Demonstrations - Andi Lutfi; Dhea Suci Wulandari; Nanda Aisyah Kurniati; Mochammad Ramadhan Nawawi Kurniawan; Rayi Rabani Azahra; Fadila Rahmadina; Muhamad Parhan (UIN Sunan Kalijaga Yogyakarta, 2026)
Student demonstrations accompanied by violent behavior remain a persistent social issue in Indonesia, particularly within university settings. This study aims to analyze the roles of psychological safety (PS) and wasathiyah (W) in predicting students’ rejection of violence (NK) at Universitas Pendidikan Indonesia (UPI). A quantitative cross-sectional survey design was employed using a non-probability convenience–snowball sampling approach. Data were collected from 51 respondents across faculties via an online Likert-scale questionnaire (1–5). Hierarchical linear regression analysis was conducted using Python’s pandas, pingouin, and statsmodels packages. The results revealed that the inclusion of PS and W significantly improved the model’s explanatory power (R² = 0.766; ΔR² = 0.6456; p < 0.001). However, only Wasathiyah showed a strong and significant effect on rejection of violence (B = 0.905; SE = 0.140; p < 0.001), whereas Psychological Safety was non-significant (B = 0.233; p = 0.223). These findings indicate that the internalization of religious moderation values plays a dominant role in reducing students’ violent tendencies, while psychological safety functions more as a contextual condition that supports the development of those values. Practically, strengthening religious moderation education alongside creating a psychologically safe and inclusive academic climate is essential to fostering a peaceful, tolerant, and non-violent campus culture.